2006
DOI: 10.1242/jcs.02847
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane recycling pathway and cell polarity in plants: studies on PIN proteins

Abstract: Results AtPIN labelled PIN proteins in root cellsWestern blot analysis The purified AtPIN antiserum labelled one major band of approximately 68-70 kDa (Fig. 1), on western blots of wholeThe PIN-FORMED (PIN) proteins are plasma-membraneassociated facilitators of auxin transport. They are often targeted to one side of the cell only through subcellular mechanisms that remain largely unknown. Here, we have studied the potential roles of the cytoskeleton and endomembrane system in the localisation of PIN proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 41 publications
10
136
1
Order By: Relevance
“…3) using an anti-AtPIN1 monoclonal antibody (Boutte et al, 2006). This antibody was previously tested in maize and was shown to specifically recognize all the different ZmPIN1 polypeptides ; data not shown).…”
Section: Zmpin1 Transcripts and Protein Localization During Endospermmentioning
confidence: 99%
See 1 more Smart Citation
“…3) using an anti-AtPIN1 monoclonal antibody (Boutte et al, 2006). This antibody was previously tested in maize and was shown to specifically recognize all the different ZmPIN1 polypeptides ; data not shown).…”
Section: Zmpin1 Transcripts and Protein Localization During Endospermmentioning
confidence: 99%
“…Material was previously fixed in 4% paraformaldehyde in 13 phosphate-buffered saline (PBS) for 16 h at 4°C. Embedded kernels were cut with a Leica RM2135 microtome and stained overnight with the anti-AtPIN1 antibody (Boutte et al, 2006) at a 1:200 dilution in 13 PBS and 1% bovine serum albumin. Subsequently, the sections were washed twice for 10 min in 13 PBS and stained for 1 h with the secondary antibody (anti-rabbit IgG conjugated with Alexa568; Molecular Probes) diluted 1:400 in 13 PBS.…”
Section: Immunolocalizationmentioning
confidence: 99%
“…S9 A and B), suggesting that RMD may regulate OsPIN protein trafficking. Because the cytoskeleton modulates protein trafficking by modifying endocytosis and exocytosis (3,4,20,(28)(29)(30), to reveal whether the OsARF23/24-RMD pathway controls endocytosis, we examined root cells using FM4-64, a tracer for endocytosis and vesicle trafficking (20,21,30). Treatment with FM4-64 for 30 min resulted in more labeled endocytic vesicles in rmd-1, osarf23, and OsARF23/24 DRi plants than WT (Fig.…”
Section: Heterodimers Ofmentioning
confidence: 99%
“…A role for COP1 in the regulation of root growth by light, through affecting the organization of the actin cytoskeleton (Dyachok et al, 2011), has also been demonstrated. Actin is known to be essential for the intracellular trafficking of PIN proteins (Geldner et al, 2001;Boutté et al, 2006) and COP1 could affect PIN1 and PIN2 intracellular localization by modulating the activity of the actin cytoskeleton. Elucidating the mode of action of COP1 will need further experiments but our findings suggest an elegant model that explains how light regulates shoot-to-root PAT and auxin distribution over the entire plant to coordinate root and shoot development in response to light in a COP1-dependent manner (supplementary material Fig.…”
Section: Research Articlementioning
confidence: 99%